2018
DOI: 10.1111/coa.13198
|View full text |Cite
|
Sign up to set email alerts
|

Measuring otoplasty outcome: Expanding the validity to caregivers' perspective and to Portuguese‐speaking children

Abstract: The Portuguese GBI and GCBI proved to be valid and reliable to evaluate HRQoL following otoplasty in Portuguese-speaking children. The outcome was very favourable; almost all patients would recommend the surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…8 However, in the validation of the Portuguese version, 2 subscales (psychosocial health and physical health) were found to account for 66.85% of the variance. 9 The high benefit derived from CIs was similar to those reported by previous studies in the literature. 10 Using the GCBI, Dev et al 11 reported improved QOL in 69 children after CIs.…”
supporting
confidence: 88%
“…8 However, in the validation of the Portuguese version, 2 subscales (psychosocial health and physical health) were found to account for 66.85% of the variance. 9 The high benefit derived from CIs was similar to those reported by previous studies in the literature. 10 Using the GCBI, Dev et al 11 reported improved QOL in 69 children after CIs.…”
supporting
confidence: 88%
“…We have chosen to name the 4 factors “Psycho-social,” “Physical health,” “Behavior” and “Vitality” based on item content and their resemblance to the original and translated factors. 1,13,20…”
Section: Resultsmentioning
confidence: 99%
“…It has been used primarily in otolaryngology, including studies on such diverse topics as correction of prominent ears, 3 turbinate surgery, 4 cochlear implantation, 5 bone anchored hearing aids, 6 tonsillectomy, 7 and drooling of saliva, 8 but has also been used in studies of constipation and faecal incontinence, 9,10 robot-assisted pyeloplasty 11 and secondary vaginoplasty for disorders of sexual development. 12 It has been translated into German, [13][14][15][16] Italian, 17 Dutch, 18,19 Spanish, 11 Portuguese, 20 Swedish, 21 Greek, 22 Turkish, 23 Russian, 24 and Mandarin Chinese. 25 Although there is some value in reporting a total score from a measure such as the GCBI, it is possible to provide more detailed information on the specific areas of patient benefit by reporting sub-scales.…”
Section: Introductionmentioning
confidence: 99%
“…The GBI is an 18-item questionnaire, designed for post-interventional health-related quality of life (HRQoL) changes in ORL procedures. It has been validated and translated into several languages (Sanchez-Cuadrado et al 2015, Aldriweesh et al 2017, Dias-Vaz et al 2018. A validation of the Swedish version of the GBI was recently published (Redfors et al 2019).…”
Section: Health-related Quality Of Life Assessment Of Cholesteatoma Smentioning
confidence: 99%